Reclassification of BRCA2 Variants of Uncertain Significance Using Saturation Genome Editing Combined with Clinical Phenotypes in Breast Cancer - Yueran Shen; Jiuan Chen; Li Hu; Jie Sun; Juan Zhang; Lu Yao; Ye Xu; Yuntao Xie (Current Oncology, 2026)
Purpose: To evaluate the pathogenicity of BRCA2 variants of uncertain significance (VUS) located within the functionally critical exons 15–26 using published SGE data, and to reclassify these VUS by integrating clinical phenotypes. Methods: A total of 15,092 breast cancer patients were enrolled in this study, among which 457 distinct BRCA2 VUS were identified in 1051 carriers. Based on SGE scores, 88 BRCA2 VUSs within exons 15–26 were functionally assessed and carriers reclassified as functionally pathogenic, functionally benign, or remaining VUS. Clinicopathological characteristics were subsequently compared across variant groups. Results: Of these 88 evaluated BRCA2 VUSs (187 carriers), 15 were reclassified as functionally pathogenic (20 carriers), 66 as functionally benign (154 carriers), and 7 remained VUS (13 carriers). Compared with non-carriers, carriers with functionally pathogenic variants exhibited a significantly higher prevalence of a family history of any cancer (65.0% vs. 31.1%, p = 0.002), particularly breast and/or ovarian cancer (35.0% vs. 10.0%, p = 0.002), as well as a trend toward a higher incidence of bilateral breast cancer (10.0% vs. 2.4%, p = 0.085). In contrast, individuals harboring functionally benign variants demonstrated clinicopathological characteristics similar to non-carriers. Conclusion: SGE-based functional scoring system provides a reliable approach for reclassifying BRCA2 VUS. When integrated with clinical phenotypes, it enhanced the accuracy of pathogenicity assessment.